Design and development of a heatsink for thermo-electric power harvesting in aerospace applications. (23rd September 2019) - Boccardi, Salvatore; Ciampa, Francesco; Meo, Michele
Abstract: In recent years, the growing interest of aerospace companies in wireless structural health monitoring (SHM) systems has led to the research of new energy efficient sources and power harvesting solutions. Among available environmental power sources, temperature gradients originated at different locations of the aircraft can be used by thermo-electric generators (TEGs) to create electrical voltage. TEGs are lightweight, provide high-energy conversion and do not contain movable parts. Thermal diffusion systems, commonly known as heatsinks, can be combined with TEGs to enhance their performance by increasing heat dissipation from a high temperature surface to the ambient air. This paper focused on the enhancement of TEG performance by developing an air-cooled heatsink for low-power wireless SHM applications. The design, manufacturing and testing of the proposed thermal diffusion system was investigated by evaluating the increase of the temperature gradient between the opposite surfaces of a commercial TEG element. The thermal performance of the heatsink was assessed with numerical finite element thermal simulations and validated with experimental tests. Experimental results revealed that the proposed thermal diffusion system provided higher temperature differences and, therefore, higher output power in comparison with traditional cylindrical pin-fin heatsinks. A hybrid heat diffusion system composed by copper heatsinks and highly oriented pyrolytic graphite layers was also here proposed in order to allow TEG reaching wireless SHM operative power requirements of tens of mW and, at the same time, adapt the assembly to the complexity of aerospace SHM arrangements. Experimental results revealed that the proposed heatsink-TEG arrangement was able to generate an output power over 25 mW.